Logging the Abbot: Reflection-Oriented XSLT Programming for Corpora Conversion and Verification - Brian L. Pytlik Zillig (Journal of the Text Encoding Initiative)
This article describes an XSLT-based logging framework developed for Abbot, a markup conversion and interoperability tool. Abbot logs structural and textual divergence from an XML source. Logging is a useful component of verification when there are too many text alterations, or too many texts, to verify closely and individually. Abbot’s conversion and logging transformations are built inside XSLT templates which are self-identifying, self-describing, and self-differencing. Abbot’s templates identify themselves and indicate where in a source text they made any changes. Moreover, they describe what they do and perform a differencing function to calculate divergences between element names, attribute names, and the contents of text nodes.